PENGARUH METODE LATIHAN TABATA WATER TRAINING DALAM MENINGKATKAN KECEPATAN RENANG 50 METER GAYA KUPU - Wing Prasetya Kurniawan (YLPK Mahardhika, 2025)
Swimming speed is determined by the accuracy in setting training zones, meeting energy requirements, and the training distance targeted by swimmers. In addition, physiological adaptations, including aerobic and anaerobic capacity, play an important role in improving the performance of swimmers. This study aims to determine the effect of the High Intensity Interval Training (HIIT) programme on improving the speed of swimming 50 metres freestyle. The research method used was quasi-experimental with a one group pretest-posttest design. The population and sample consisted of 16 swimmers from the Sailfish Swimming Club who were selected using purposive sampling. Data analysis was performed using a t-test. The results showed a significant improvement, with a significance value of 0.000 < 0.05, where the average swimming time in the pretest was 38.64 seconds and increased in the posttest to 36.97 seconds.